Shaping The Way to Teach? Exploring the Adoption of Digital Multimodal Texts As Instructional Tools in EFL Teaching Practicum - Widyaningrum, Lulut; Fadhilah, Ma'rifatul; Sholihah, Nurus; Rochmawati, Pryla (Language Circle: Journal of Language and Literature, 2024)
This research scrutinizes a case study conducted with 15 pre-service English as a Foreign Language (EFL) teachers in a microteaching class at the English Education Department at UIN Walisongo Semarang. The purpose of the study was to examine the forms, implementation, and reflection of digital multimodal instructional media utilized by pre-service teachers. Observations of classrooms and document analysis were employed to acquire data. Pre-service EFL teachers employ digital multimodal instructional media, including PowerPoint presentations, films, and songs, to enhance English language learning. These tools integrate text, images, video, and audio elements to teach language structures, vocabulary, and emotions effectively. Student portfolios showcase diverse educational strategies across different grade levels, using videos, songs, and PowerPoint presentations to engage students and reinforce language skills. Educator reflections underline the significance of digital multimodal media in simplifying complex topics, improving comprehension, and fostering a holistic learning experience. They also stress the importance of adequate equipment and resources for successful multimedia implementation, affirming the value of multimodal approaches in providing impactful and engaging English language education. The study highlights the potential for these digital tools to provide an engaging and interactive learning environment for EFL students. It is recommended that more research investigate ways for optimizing the use of digital multimodal media in diverse EFL teaching scenarios.